COMPARATIVE STUDY OF ISLAMIC EDUCATION CURRICULUM INTEGRATION AT SMP AL-ISTIQOMAH AND CHARIYATHAMSUKSA SCHOOL - Mustika Dewi; Siti Khusniyati Sururiyah; Siti Wulan Asih (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
This study aims to describe and compare the models of Islamic Religious Education (IRE) curriculum integration implemented at SMP Unggulan Al-Istiqomah (Indonesia) and Chariyathamsuksa Foundation School (Thailand) from conceptual, practical, and socio-cultural perspectives. Employing a comparative qualitative approach with a descriptive-analytic design, data were collected through interviews, observations, and document analysis. The findings indicate that SMP Unggulan Al-Istiqomah applies a thematic-holistic integration model that combines the Kurikulum Merdeka with a pesantren-based system. Islamic values are embedded across subjects through the Contextual Teaching and Learning (CTL) approach and character-building activities such as worship routines, Qur’an memorisation, and spiritual reflection. In contrast, Chariyathamsuksa Foundation School adopts a structural-adaptive model with a dual curriculum system that integrates the Thai national curriculum with Islamic Diniyyah education. This model emphasises contextual adaptation within a plural society through bilingual learning and cross-subject integration. The main difference lies in the social context: Indonesia’s Muslim-majority setting enables complete internalisation of Islamic values, while Thailand’s Muslim-minority context requires adaptive strategies under a secular education framework. Despite these differences, both models share the same vision of nurturing students with religious character, intellectual competence, and a balanced integration of faith and knowledge. The study concludes that Islamic curriculum integration should be developed contextually, responsively, and in harmony with each nation’s socio-cultural setting.